2013
DOI: 10.1021/bi400141u
|View full text |Cite
|
Sign up to set email alerts
|

A Route from Darkness to Light: Emergence and Evolution of Luciferase Activity in AMP-CoA-Ligases Inferred from a Mealworm Luciferase-like Enzyme

Abstract: The origin of luciferases and of bioluminescence is enigmatic. In beetles, luciferases seem to have evolved from AMP-CoA-ligases. How the new oxygenase luminogenic function originated from AMP-ligases leading to luciferases is one of the most challenging mysteries of bioluminescence. Comparison of the cloned luciferase-like enzyme from the nonluminescent Zophobas morio mealworm and beetle luciferases showed that the oxygenase activity may have emerged as a stereoselective oxidative drift with d-luciferin, a su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 37 publications
0
16
0
1
Order By: Relevance
“…However, all insects express longchain fatty acyl-CoA synthetases (ACSLs) that share high homology to beetle luciferases and are hypothesized to be their evolutionary antecedents (4)(5)(6). These two classes of enzymes are both members of the adenylate-forming superfamily (7) and share the ability to make AMP esters of fatty acids as well as the ability to displace the AMP ester with CoASH ( Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, all insects express longchain fatty acyl-CoA synthetases (ACSLs) that share high homology to beetle luciferases and are hypothesized to be their evolutionary antecedents (4)(5)(6). These two classes of enzymes are both members of the adenylate-forming superfamily (7) and share the ability to make AMP esters of fatty acids as well as the ability to displace the AMP ester with CoASH ( Fig.…”
mentioning
confidence: 99%
“…Beetle luciferases differ from other insect ACSLs in their ability to chemically generate light by adenylating and oxidizing D-luciferin, a small molecule naturally found in bioluminescent beetles. How this additional activity developed is unknown, although weak bioluminescence has been reported by treating a beetle ACSL with D-luciferin (6,9).…”
mentioning
confidence: 99%
“…The cDNA of the luciferase-like ligase was cloned, and the enzyme structure and function determined by Viviani et al (2013). The authors concluded that luciferases may have evolved from ligases by mutagenesis of amino acids located in the activity site that enable them to act as a luminogenic monoxidase.…”
Section: The Luciferase Origin Of Beetle Bioluminescencementioning
confidence: 99%
“…The authors concluded that luciferases may have evolved from ligases by mutagenesis of amino acids located in the activity site that enable them to act as a luminogenic monoxidase. Mutations of the so-called "protoluciferases" may engender new chemiluminescence-eliciting ligases, capable of using various carboxylic acids as substrates and drawing forth different emission colors (Prado et al 2011, Viviani et al 2013. These findings may significantly expand the analytical applications of engineered luciferases and AMP-CoA ligases (Roda 2011, Li et al 2010, Shimomura 2012.…”
Section: The Luciferase Origin Of Beetle Bioluminescencementioning
confidence: 99%
“…[44][45][46] Em ambos os casos -luciferase e ligase -, o papel do ATP é ativar a carboxila na forma de um adenilado (anidrido misto), um excelente grupo de partida em ataques nucleofílicos: à carbonila no caso da luciferase, ou um tioéster nos casos de proteínas e gliceróis, também um excelente g upoà deà saídaà aoà ata ueà doà α-aminogrupo do aminoácido a ser inserido na cadeia crescente do peptídeo, ou do grupo hidroxila do glicerol receptor do grupo acila. 45 A propósito, em anos recentes foi relatada a ação catalítica de luciferase sobre a acilação de glicerol por ácidos graxos, permitindo o desenvolvimento de métodos analíticos para a determinação de ácidos carboxílicos e triacilgliceróis em soro.…”
Section: Ligases Versus Luciferases: Uma Proposta Para a Evolução Da unclassified